Asymmetric syntheses of (R)-4-halo-6, 6a, 7, 8, 9, 10-hexahydro-5H-pyrazino[1, 2-a][1, n]naphthyridines, important 5-HT2C agonist precursors. Issue 21 (23rd May 2018) - Schrader, Thomas O.; Zhu, Xiuwen; Kasem, Michelle; Li, Sufang; Liu, Chunyan; Ren, Albert; Wu, Chunrui; Semple, Graeme
Graphical abstract: Highlights: Novel chiral tricyclic tetrahydronaphthyridine-based tricyclic amines are described. Compounds are valuable synthetic precursors to potent and selective 5-HT2C agonists. Ring opening of fused bicyclic sulfamidate with dihalopyridinyllithiums. Chemoselective intramolecular SN Ar reaction. Abstract: Asymmetric syntheses of N -protected ( R )-4-halo-6, 6a, 7, 8, 9, 10-hexahydro-5 H -pyrazino[1, 2- a ][1, n ]naphthyridines, advanced intermediates for the synthesis of highly potent and selective 5-HT2C agonists, are described. The key transformation involves ring opening of N -protected bicyclic sulfamidate ( R )-hexahydro-3 H -pyrazino[1, 2- c ][1, 2, 3]oxathiazine 1, 1-dioxide with (4-halo-2-fluoropyridin-3-yl)lithiums or (3-bromo-5-fluoropyridin-4-yl)lithium. In situ hydrolyses of the resultant sulfamic acids and subsequent intramolecular nucleophilic aromatic substitutions (SN Ar) produce the enantiopure tricycles. The two step procedure represents new methodology for the stereoselective syntheses of tetrahydronaphthyridines.